Primary type status of Perca cirrosa Thunberg, 1793 (Scorpaenidae) - Motomura, Hiroyuki; Takigawa, Yuko; Ogihara, Gota; Yoshino, Tetsuo (Zootaxa, 2011)
The Indo-Pacific scorpionfish genus Scorpaenopsis was revised by Randall and Eschmeyer (2001), who recognized 24 valid species in the genus. Subsequently, Randall and Greenfield (2004), Motomura (2004a) and Motomura and Causse (2011) described S. eschmeyeri, S. insperatus and S. crenulata, respectively, being new species from the southwestern Pacific Ocean.